Limb Salvage Surgery: An Advance in Surgical Technique - McCulloch, Wendy (Operating Room Nurses Association of Canada Journal, 1994)
“Surgery is the primary and oldest treatment for malignant musculoskeletal tumors. Until the 1970’s amputation was the accepted surgical procedure for patients with malignant tumors of the extremities. Recent advances in adjuvant treatment modalities such as chemotherapy and radiotherapy, bioengineering de- signs of internal prosthetic devices, radiographic workups, and bone and tissue transfers provide some individuals with the option of limb-preservation” (Lewis, 1992, p. 477-478). One limb salvaging technique uses a metallic implant to replace resected tumors of the bone. It is this surgical orthopaedic advancement that is currently being used in the resection of primary malignantbone tumors of the lower extremeties at Mount Sinai Hospital, Toronto, Ontario.